MANFAAT OLAHAN TOGA UNTUK PENGOBATAN DI DESA DELIKSUMBER KECAMATAN BENJENG KABUPATEN GRESIK - Ridwan, Agus (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Health care are sought by everyone. one way to keep your body in good health is a stylish way of life that is clean, healthy, and able to maintain physical fitness. In addition, people can take advantage of traditional crops that can be used for example medicines that can address health issues. Traditional medicine has good benefits to health and does not give a fatal side effects for health. Plants that are around us can be useful for healing or prevention of disease in the suffering. This research is a qualitative research. This research method is observation. This research was conducted in the village MetatuBenjeng District of Gresik on February 1, 2017 - March 1, 2017. To be used by residents and surrounding communities metatu us as researchers hold TOGA processing in village districts Metatu Benjeng Gresik regency. The results of this study indicate that there is enough of the citizens Metatu can process and utilize plant TOGA. It can be concluded that the community has been eager to apply this in everyday life. Researchers hope the people of the village Metatu will be able to add their insight on TOGA crop plants so that they can take advantage of toga over again and they are also able to process them